PENINGKATAN HASIL BELAJAR DENGAN MODEL PICTURE AND PICTURE PADA PEMBELAJARAN MATEMATIKA BAGI SISWA KELAS VI SDN KALICARI 01 - Achmad Triyanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to improve student learning outcomes in learning mathematics with the Picture and Picture model. This study used a Classroom Action Research (CAR) design which was carried out for two cycles. The stages of conducting research include planning, implementing, observing, and reflecting. This study shows that student learning outcomes have increased in each cycle. At the pre-cycle stage, the average learning completeness was only 25%, in the first cycle, the average learning mastery was 65.5%, in the second cycle, the learning mastery average was 93.5%. It can be concluded that student learning outcomes with the Picture and Picture model in mathematics learning which starts from the pre-cycle, cycle I, and cycle II have increased.